2020
DOI: 10.1038/s41598-020-71063-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aPTT-based clot waveform analysis for the detection of haemostatic changes in different types of infections

Abstract: Infections cause varying degrees of haemostatic dysfunction which can be detected by clot waveform analysis (CWA), a global haemostatic marker. CWA has been shown to predict poor outcomes in severe infections with disseminated intravascular coagulopathy. The effect of less severe bacterial and viral infections on CWA has not been established. We hypothesized that different infections influence CWA distinctively. Patients admitted with bacterial infections, dengue and upper respiratory tract viral infections we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…In our study, we expected to find more severe hemostatic disturbances in meningococcal infections, but only higher levels of thrombomodulin were observed for meningococcal infections. Similar to our study, Tan et al ( 44 ) found that patients with different types of bacterial infections had alterations in hemostatic mechanisms measured by clot waveform analysis. Differences between Gram-positive infections and Gram-negative infections were also not observed in their study, although they included a different variety of pathogens and did not include N. meningitidis .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we expected to find more severe hemostatic disturbances in meningococcal infections, but only higher levels of thrombomodulin were observed for meningococcal infections. Similar to our study, Tan et al ( 44 ) found that patients with different types of bacterial infections had alterations in hemostatic mechanisms measured by clot waveform analysis. Differences between Gram-positive infections and Gram-negative infections were also not observed in their study, although they included a different variety of pathogens and did not include N. meningitidis .…”
Section: Discussionsupporting
confidence: 91%
“…To further evaluate the thrombotic potential in COVID-19, we analysed available CWA parameters as a global haemostatic assessment. It has been reported that CWA parameters differ in various types of infections 34 and increased CWA is associated with hypercoagulability 35 , 36 . Our findings suggest that there were no significant changes in the overall haemostatic functions in mild COVID-19 but severe COVID-19 was associated with a prothrombotic state and this hypercoagulability gradually normalizes during the convalescent phase.…”
Section: Discussionmentioning
confidence: 99%
“…Some trials have comprehensively used CWA to predict hemostatic effects in emicizumab prophylaxis. 7,18,19 Further, CWA can be used to obtain specific parameters even in infections without disseminated intravascular coagulation (DIC), to distinguish bacterial or viral infection and facilitate selection and early administration of optimal antibiotics for each infection 20 ; moreover, CWA has been associated with the diagnosis of COVID-19, pathological conditions, and prognosis prediction. 21,22 CWA can reflect the entire process of clot formation and is expected to be clinically applied for the differential diagnosis of diseases, severity determination, prognosis prediction, and treatment monitoring in the future.…”
Section: Discussionmentioning
confidence: 99%